Impact of new consent procedures on uptake of the schools-based human papillomavirus (HPV) vaccination programme. (26th September 2020) - Fisher, Harriet; Hickman, Matthew; Ferrie, Joanne; Evans, Karen; Bell, Michael; Yates, Julie; Roderick, Marion; Reynolds, Rosy; MacLeod, John; Audrey, Suzanne
Abstract: Background: Local policy change initiating new consent procedures was introduced during 2017–2018 for the human papillomavirus (HPV) vaccination programme year in two local authorities in the south–west of England. This study aims to assess impact on uptake and inequalities. Methods: Publicly available aggregate and individual-level routine data were retrieved for the programme years 2015–2016 to 2018–2019. Statistical analyses were undertaken to show: (i) change in uptake in intervention local authorities in comparison to matched local authorities and (ii) change in uptake overall, and by local authority, school type, ethnicity and deprivation. Results: Aggregate data showed uptake in Local Authority One increased from 76.3% to 82.5% in the post-intervention period (risk difference: 6.2% P = 0.17), with a difference-in-differences effect of 11.5% ( P = 0.03). There was no evidence for a difference-in-differences effect in Local Authority Two ( P = 0.76). Individual-level data showed overall uptake increased post-intervention (risk difference: +1.1%, P = 0.05), and for young women attending school in Local Authority One (risk difference: 2.3%, P < 0.01). No strong evidence for change by school category, ethnic group and deprivation was found. Conclusion: Implementation of new consent procedures can improve and overcome trends for decreasing uptake among matched local authorities. However, no evidence for reduction in inequalities was found. Implications and discussion: The new consent procedures increased uptake in one of the intervention sites and appeared to overcome trends for decreasing uptake in matched sites. There are issues in relation to the quality of data which require addressing.